BIOLOGICAL NOTES ON KING MACKEREL, SCOMBEROMORUS CAVALLA (CUVIER), FROM NORTHEASTERN BRAZIL - Nomura, Hitoshi; Rodrigues, Maria Sílvia de Sousa (Arquivos de Ciências do Mar, 2018)
The main species of fish of commercial importance in northeastern Brazil is the king mackerel Scomberomorus cavalla (Cuvier). It is fund in the western Atlantic, from Maine to Brazil (Robins, 1958) . Some biological notes on the king mackerel are given in this paper, concerning its condition factor, age and growth in terms of fork length and weight.